2003
DOI: 10.1046/j.1365-313x.2003.01845.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functional lox sites in the plastid genome

Abstract: SummaryOur objective was to test whether or not cyclization recombination (CRE), the P1 phage site-speci®c recombinase, induces genome rearrangements in plastids. Testing was carried out in tobacco plants in which a DNA sequence, located between two inversely oriented locus of X-over of P1 (loxP) sites, underwent repeated cycles of inversions as a means of monitoring CRE activity. We report here that CRE mediates deletions between loxP sites and plastid DNA sequences in the 3 H rps12 gene leader (lox-rps12 ) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Testing Cre-mediated marker gene excision revealed fortuitous ptDNA sequences or pseudo lox sites in the plastid genome that are recognized by the Cre. As the consequence, when a loxP site is present, Cre mediates deletions between loxP and lox-rps12 or loxP and lox-psbA sequences (Corneille et al 2003). In this study no deletions were found on DNA blots that would be indicative of recombination between attP or attB sequences and fortuitous ptDNA sequences that function as pseudo-attP or pseudo-attB sites.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Testing Cre-mediated marker gene excision revealed fortuitous ptDNA sequences or pseudo lox sites in the plastid genome that are recognized by the Cre. As the consequence, when a loxP site is present, Cre mediates deletions between loxP and lox-rps12 or loxP and lox-psbA sequences (Corneille et al 2003). In this study no deletions were found on DNA blots that would be indicative of recombination between attP or attB sequences and fortuitous ptDNA sequences that function as pseudo-attP or pseudo-attB sites.…”
Section: Discussionmentioning
confidence: 48%
“…When excision of the marker gene is required, a plastid-targeted cre gene is expressed in the nucleus and the Cre protein is imported into chloroplasts where it excises the plastid marker gene (Corneille et al 2001;Hajdukiewicz et al 2001;Lutz et al 2006a). Problems encountered with Cre-mediated marker excision were recombination of loxP sequences with fortuitous pseudo lox sites in the plastid genome (Corneille et al 2003), and enhanced homologous recombination adjacent to loxP sites that resulted in the loss of ptDNA segments between directly repeated sequences (Corneille et al 2001;Tungsuchat et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…INT-mediated excision was confirmed by DNA gel-blot analyses. The functionality of loxP sites flanking the bar au gene in Nt-pSS42 plants was shown by excision of the bar au gene by the Cre recombinase after cocultivation with Agrobacterium carrying plasmid pKO31 and confirmed by DNA gel-blot analyses (Corneille et al, 2003).…”
Section: Transformation Of the Nucleus With Genes Encoding Plastid-tamentioning
confidence: 96%
“…Site-specific Cre-mediated recombination has been shown to occur between sites of varying degrees of sequence similarity to loxP with a high frequency in vitro (Hoess et al, 1982;Sauer, 1992Sauer, , 1996Thyagarajan et al, 2000;Corneille et al, 2003). Cryptic sites containing as few as 14 out of 34 bases in common with loxP have been shown to be effective (Sauer, 1996;Siegel et al, 2001;Chatterjee et al, 2010).…”
Section: (I) Exposure To Dnamentioning
confidence: 99%